Analysis Monetize Strategy of EZ Marker Technology Product - Ramadan Pandu Setia Negara Siregar, Ilham; Meuthia Pratiwi, Putri; Irna Setiawati, Cut (International Journal of Engineering and Technology, 2019)
In this era of Technology, Indonesian education needs advanced technology to support the Human Resource. In addition, According to the data is from Indonesia Cell Phone Association (APSI) Indonesia has around 55.4 milion smartphone users. This fact should be used as a turning point of knowledge transformation process. Moreover, this paper discusses a new product innovation for efficient and effective online method of correcting answer sheets using android computer and website. This application is EZ Marker. Ez Marker has gone through trial processes external validation acquired in SD Negeri 02 (2 nd Elementary School) of Sukapura, Bandung, Indonesia. However, it has not had any Monetize strategy. The purpose of this paper is to find out the users' willingness to buy the product using the EZ Marker analysis theory of Freemium Model. Furthermore, the critical review and descriptive methods are required. The result of this paper will provide references of the startups in Indonesia, since the quantity of ASEAN startups is quite high as well as the users of technology. With user development analysis, we hope to fulfill consumers' needs. In the end, EZ Marker will be more acceptable to Indonesian citizens especially in the education sector.Â Â